Potential sources and characteristic occurrence of mobile colistin resistance (mcr) gene-harbouring bacteria recovered from the poultry sector: a literature synthesis specific to high-income countries - Madubuike Umunna Anyanwu (PeerJ, 2021)
Understanding the sources, prevalence, phenotypic and genotypic characteristics of mcr gene-harbouring bacteria (MGHB) in the poultry sector is crucial to supplement existing information. Through this, the plasmid-mediated colistin resistance (PMCR) could be tackled to improve food safety and reduce public health risks. Therefore, we conducted a literature synthesis of potential sources and characteristic occurrence of MGHB recovered from the poultry sector specific to the high-income countries (HICs). Colistin (COL) is a last-resort antibiotic used for treating deadly infections. For more than 60 years, COL has been used in the poultry sector globally, including the HICs. The emergence and rapid spread of mobile COL resistance (mcr) genes threaten the clinical use of COL. Currently, ten mcr genes (mcr-1 to mcr-10) have been described. By horizontal and vertical transfer, the mcr-1, mcr-2, mcr-3, mcr-4, mcr-5, and mcr-9 genes have disseminated in the poultry sector in HICs, thus posing a grave danger to animal and human health, as harboured by Escherichia coli, Klebsiella pneumoniae, Salmonella species, and Aeromonas isolates. Conjugative and non-conjugative plasmids are the major backbones for mcr in poultry isolates from HICs. The mcr-1, mcr-3 and mcr-9 have been integrated into the chromosome, making them persist among the clones. Transposons, insertion sequences (IS), especially ISApl1 located downstream and upstream of mcr, and integrons also drive the COL resistance in isolates recovered from the poultry sector in HICs. Genes coding multi-and extensive-drug resistance and virulence factors are often co-carried with mcr on chromosome and plasmids in poultry isolates. Transmission of mcr to/among poultry strains in HICs is clonally unrestricted. Additionally, the contact with poultry birds, manure, meat/egg, farmer’s wears/farm equipment, consumption of contaminated poultry meat/egg and associated products, and trade of poultry-related products continue to serve as transmission routes of MGHB in HICs. Indeed, the policymakers, especially those involved in antimicrobial resistance and agricultural and poultry sector stakeholders-clinical microbiologists, farmers, veterinarians, occupational health clinicians and related specialists, consumers, and the general public will find this current literature synthesis very useful.